2006
DOI: 10.1063/1.2171965
|View full text |Cite
|
Sign up to set email alerts
|

Free energy of a trans-membrane pore calculated from atomistic molecular dynamics simulations

Abstract: Atomistic molecular dynamics simulations of a lipid bilayer were performed to calculate the free energy of a trans-membrane pore as a function of its radius. The free energy was calculated as a function of a reaction coordinate using a potential of mean constraint force. The pore radius was then calculated from the reaction coordinate using Monte Carlo particle insertions. The main characteristics of the free energy that comes out of the simulations are a quadratic shape for a radius less than about 0.3 nm, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
194
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(226 citation statements)
references
References 49 publications
28
194
4
Order By: Relevance
“…The line tensions at the perimeter of the bilayer fold, p , were calculated from simulation of a semiperiodic bilayer slab in water. The obtained values are in agreement with previous simulations (50 pN) (33) and somewhat larger than experimental values (5-30 pN) (34,35). The line tension at the bilayer connection to the monolayer, c, was obtained from simulations of monolayers connected by a bilayer.…”
Section: Structure Of Lipid Aggregates Formed Upon Monolayer Collapsesupporting
confidence: 81%
“…The line tensions at the perimeter of the bilayer fold, p , were calculated from simulation of a semiperiodic bilayer slab in water. The obtained values are in agreement with previous simulations (50 pN) (33) and somewhat larger than experimental values (5-30 pN) (34,35). The line tension at the bilayer connection to the monolayer, c, was obtained from simulations of monolayers connected by a bilayer.…”
Section: Structure Of Lipid Aggregates Formed Upon Monolayer Collapsesupporting
confidence: 81%
“…3 Briels and colleagues determined the free energy profile for a pore in a dipalmitoylphosphatidylcholine membrane using atomistic molecular dynamics simulations and reported that no energy barrier exists between intact state O and state I, which supports model B. 13,14 Recently, Evans and Smith reported that the energy profile for a lipid membrane containing a pre-pore depends on the types of lipids composing the membrane. 4 The results of the present study clearly indicate that a free energy which does not depend on tension, U 0 , contributes significantly to U a based on the experimental results (not based on interpretation).…”
Section: Discussionmentioning
confidence: 99%
“…3(a-3)). [12][13][14][15] When the radius is small, the pre-pore is hydrophobic, but as the radius expands and reaches a critical value, the prepore becomes hydrophilic. [12][13][14][15] Atomistic molecular dynamics simulation results 13,14 indicate the structure of a hydrophilic pre-pore shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the recent advance of computational approaches, researchers have investigated pore formation on membranes using Monte Carlo simulations and molecular dynamics (MD) simulations, which can reveal the molecular process of pore formation (26)(27)(28)(29)(30). In a number of MD simulation studies, the TMP was conveniently modeled by an external electric field across the membranes without any involvement of ions (26,27).…”
Section: Introductionmentioning
confidence: 99%